2012
DOI: 10.1007/s00540-012-1537-9
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan is superior to dobutamine as an inodilator in the treatment of pulmonary hypertension for children undergoing cardiac surgery

Abstract: Levosimendan is better than dobutamine for treatment of pulmonary hypertension of children undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 22 publications
1
60
0
1
Order By: Relevance
“…61,62 However, in another case report of patients with idiopathic pulmonary arterial hypertension, levosimendan failed to reduce PAP. 63 Levosimendan has been shown to be superior to dobutamine in some patient groups: in children with PH undergoing cardiac surgery 64 and in patients with biventricular failure levosimendan improves ejection fraction and tricuspid annular plane systolic excursion, decreasing systolic PAP. 65 Nevertheless, the role that levosimendan may play in PH with preserved left ventricular function has been little investigated, particularly in chronic PH.…”
Section: Right Ventricular Dysfunction and Pulmonary Hypertensionmentioning
confidence: 98%
“…61,62 However, in another case report of patients with idiopathic pulmonary arterial hypertension, levosimendan failed to reduce PAP. 63 Levosimendan has been shown to be superior to dobutamine in some patient groups: in children with PH undergoing cardiac surgery 64 and in patients with biventricular failure levosimendan improves ejection fraction and tricuspid annular plane systolic excursion, decreasing systolic PAP. 65 Nevertheless, the role that levosimendan may play in PH with preserved left ventricular function has been little investigated, particularly in chronic PH.…”
Section: Right Ventricular Dysfunction and Pulmonary Hypertensionmentioning
confidence: 98%
“…A variety of preclinical and clinical studies suggest that levosimendan attenuates in pulmonary vascular remodelling and has antiproliferative and anti‐inflammatory effects . Preliminary data has shown that it possesses beneficial haemodynamic effects and improves right ventriculovascular coupling in patients with PH. Levosimendan has been reported to be a novel calcium‐sensitizing drug and a promising agent for PAH therapy …”
Section: Introductionmentioning
confidence: 99%
“…Alors que la CEC peut être responsable d'une réactivité pulmonaire parfois difficile à contrôler pendant la phase de réanimation, cette action sur les résistances vasculaires pulmonaires est de première importance et a été bien montrée sur un modèle pédiatrique porcin [35]. Ainsi, après une chirurgie cardiaque chez l'enfant, cet effet vasodilatateur pulmonaire semble plus prononcé pour le levosimendan que pour la dobutamine [36]. Si dans le groupe des inodilatateurs (dobutamine, enoximone, milrinone, levosimendan), le levosimendan semble donc particulièrement efficace pour le traitement du choc cardiogénique post-cardiotomie, les rares études randomisées ne permettent pas de conclure à une différence d'efficacité par rapport aux autres traitements inotropes [4,24,37,38].…”
Section: Cardiologieunclassified